2018
DOI: 10.4315/0362-028x.jfp-17-317
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacteriaceae Antibiotic Resistance in Ready-to-Eat Foods Collected from Hospital and Community Canteens: Analysis of Prevalence

Abstract: Foodborne diseases and antibiotic resistance are serious widespread health problems in the contemporary world. In this study, we compared the microbiological quality of ready-to-eat (RTE) foods found in community canteens versus hospital canteens in Rome, Italy, focusing on detection and quantification of Enterobacteriaceae and the antibiotic resistance of these bacteria. Our findings show a remarkable difference in Enterobacteriaceae contamination between RTE foods distributed in community canteens (33.5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Similar ndings have been reported by a study conducted in Italy. In their study, approximately 38% of RTE foods were contaminated with AMR bacteria due to poor hygienic processing and handling of foods (27). Our ndings are also consistent with the study conducted in Nepal, where a high prevalence of MDR foodborne bacteria was associated with non-gloved food handlers and unsanitized food utensils (28).…”
Section: Discussionsupporting
confidence: 89%
“…Similar ndings have been reported by a study conducted in Italy. In their study, approximately 38% of RTE foods were contaminated with AMR bacteria due to poor hygienic processing and handling of foods (27). Our ndings are also consistent with the study conducted in Nepal, where a high prevalence of MDR foodborne bacteria was associated with non-gloved food handlers and unsanitized food utensils (28).…”
Section: Discussionsupporting
confidence: 89%
“…Antibiotic resistance phenotypic analysis showed that 96.1% of the 77 selected isolates were MDR, while resistance to aminoglycosides (94.8%), chloramphenicol (85.7%) and tetracyclines (53.2%) was the most common. Vincenti et al [ 70 ] determined antibiotic resistance in ready-to-eat food collected from hospital and community canteens in Rome. Studies have shown that approximately 38% of RTE food supplied in municipal canteens does not meet the microbiological criteria for food safety and may pose a particular threat to consumers due to the spread of antibiotic-resistant strains.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies reported high levels of TE-resistance in enterococci (Cauwerts et al, 2007) and E. coli (Al-Bahry et al, 2013) from animal sources, DNA is partially degraded by heat, and thus, consumption of raw fresh produce is more likely to deliver a higher concentration of ARG into the gastrointestinal tract IJFS October 2021 Volume 10 pages 359-370 (Hoelzel et al, 2018). Multidrug-resistant bacteria were previously isolated from various readyto-eat foods (Vincenti et al, 2018), including fresh produce that contained multidrug-resistant enterococci (Johnston & Jaykus, 2004) and E. coli (Al-Kharousi et al, 2016). Thus, these food commodities, which usually receive no or minimal heat treatment before consumption, may act as a vehicle for transfer of multidrug-resistant enterococci or E. coli to humans (Johnston & Jaykus, 2004).…”
Section: Significance Of Te Resistance In Fresh Produce-associated Enterococci and E Colimentioning
confidence: 99%